PRIVILEGE UMAT NABI MUHAMMAD SAW MENURUT PANDANGAN IBNU KATSIR (STUDI PENAFSIRAN SURAT ALI IMRON :110) - Jauharotul Humairoh; Moch. Nurcholish (PT. Hasba Edukasi Mandiri, 2025)
Muslims are the luckiest people because they are given grace in the form of the sending of khatim al-Anbiya', namely the Prophet Muhammad who because of the existence of all creatures on earth were created including the prophet Adam A.S. in addition to being destined to be the people of the Prophet, we are blessed with several privileges that Allah has never given to the previous servants, this is not spared because of the blessing of the Prophet Muhammad who lobbies to us. Among these privileges are the praise and reward of Allah for carrying out His commands, amar ma'ruf nahi munkar and believing in Allah is the key to getting his reward as